Characterization of novel HLA class I alleles: HLA‐A*02:984, ‐B*18:205, ‐B*57:142N, ‐C*02:204, and ‐C*16:185. (29th June 2021) - Balas, Antonio; Moreno‐Hidalgo, Miguel‐Ángel; Alenda, Raquel; García‐Sanchez, Félix; Vicario, José L.
Abstract : Five new HLA class I alleles were characterized by next‐generation sequencing.